New Insights Into the Function of Flavohemoglobin in Mycobacterium tuberculosis: Role as a NADPH-Dependent Disulfide Reductase and D-Lactate-Dependent Mycothione Reductase - Thakur, Naveen; Sharma, Amar Nath; Hade, Mangesh Dattu; Chhaya, Ajay; Kumar, Ashwani; Jolly, Ravinder Singh; Dikshit, Kanak L. (Frontiers in Cellular and Infection Microbiology, 2022)
Mycobacterium tuberculosis (Mtb) produces an unconventional flavohemoglobin (MtbFHb) that carries a FAD-binding site similar to D-lactate dehydrogenases (D-LDH) and oxidizes D- lactate into pyruvate. Molecular mechanism by which MtbFHb functions in Mtb remains unknown. We discovered that the D-LDH type FAD-binding site in MtbFHb overlaps with another FAD-binding motif similar to thioredoxin reductases and reduces DTNB in the presence of NADPH similar to trxB of Mtb. These results suggested that MtbFHb is functioning as a disulphide-oxidoreductase. Interestingly, D-lactate created a conformational change in MtbFHb and attenuated its ability to oxidize NADPH. Mass spectroscopy demonstrated that MtbFHb reduces des-myo-inositol-mycothiol in the presence of D-lactate unlike NADPH, indicating that D-lactate changes the specificity of MtbFHb from di-thiol to di-mycothiol. When M. smegmatis carrying deletion in fhbII gene (encoding a homolog of MtbFHb) was complemented with the fhb gene of Mtb, it exhibited four to five fold reductions in lipid peroxidation and significant enhancement in the cell survival under oxidative stress. These results were corroborated by reduced lipid peroxidation and enhanced cell survival of wild type M. smegmatis after overexpression of the fhb gene of Mtb. Since D- lactate is a by-product of lipid peroxidation and MtbFHb is a membrane-associated protein, D-lactate mediated reduction of mycothiol-disulphide by MtbFHb may uniquely equip Mtb to relieve the toxicity of D-lactate accumulation and protect the cell from oxidative damage, simultaneously balancing the redox environment under oxidative stress that may be vital for the pathogenesis of Mtb